Financial Distress Analysis in an Indonesian Textile Company - Ramadhan, Yanuar; Marindah, Marindah (KnE Social Sciences, 2021)
This research aimed to examine the health of textile companies by using the Altman Z-Score method. The Altman model is used to determine the effect on financial distress through Working Capital to Total Asset (WCTA), Retained Earning to Total Asset (RETA), Earning Before Interest and Tax to Total Asset (EBITA), Market Value of Equity to Book Value of Liabilities (MVEBL) and Sales to Total Asset (STA). The population in this study was textile companies for the period 2016-2019. The sample was 14 textile companies with a research time of 4 years resulting in 56 samples obtained by purposive sampling. The results indicated that WCTA, RETA, EBITA, MVEBL and STA had a simultaneous effect on financial distress, but they had no effect separately. Keywords: Altman Z-Score, financial distress, bankruptcy